Corporate Governance Moderate Effect of Environmental Perfomance and Disclosure on Company Perfomance - Hendronoto Hadi Wibowo; Lodovicus Lasdi (AKRUAL: JURNAL AKUNTANSI, 2022)
The Industrial Revolution 4.0 is a revolution in technological development, this revolution helps company operational activities to be more efficient in improving company performance. In addition, companies must apply the triple bottom line (3P) principle in their operations. This research uses environmental disclosure and environmental performance with moderate variables two corporate governance mechanisms, foreign ownership and an independent board of commissioners. In this research, the companies that will be used as objects are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 to 2019. The results of research this uses provide evidence that environmental performance has effect on company performance while environmental disclosure doesn’t affect company performance. And the moderating variable, foreign ownership provides evidence that it can strengthen the relationship between environmental performance and environmental disclosure on company performance, while the independent board of commissioners cannot strengthen the relationship between environmental performance and disclosure on company performance.